Cyber war - trends and technologies - Trifunović, Darko (Array, 2021)
Cyberspace has become an indispensable part in which special operations such as cyber war or warfare take place. The role of special war as the use of so-called soft power was emphasized. The country's number of potential adversaries in cyber warfare is unlimited, making highly endangered aspects of cyber civilian infrastructure, which is essentially military readiness, including the mobilization of forces through the civilian sector, also a likely target. A special type of cyber war or warfare is hybrid warfare. This type of warfare is increasingly resorted to because it is extremely cheaper than the conventional method of warfare and at the same time brings exceptional results. The first thing that affects cyber security policy analysts comes with the issue of neutrality, as well as the huge variety of assessments about future attack and defense technologies. There is also a consideration that the new (problematic) cyber technology will be deployed in a short period of time, in time periods, in just a few days in terms of warnings. Second, is the trends in cyber-attack and defense technologies and who is following those processes. Third, decision making technology having in mind high-performance computers, technologies that are well known, although rapidly evolving, are increasingly seen as a basic means of managing cyber defense at the national military and security level, as well as a new weapon in the hands of opponents. Fourth, role of intelligence in planning future scenarios for defense against hybrid or any other cyber threat/s.